BioNoculars : Extracting relations between entities from biomedical documents using a fully unsupervised Statistical Approach - Madkour, Amgad; Hassan Awadalla, Hany; Awadallah, Ahmed; Emam, Ossama (ACL BioNLP, 2007)
The vast number of published medical documents is considered a vital source for relationship discovery. This paper presents a statistical unsupervised system, called BioNoculars, for extracting protein-protein interactions from biomedical text. BioNoculars uses graph-based mutual reinforcement to make use of redundancy in data to construct extraction patterns in a domain independent fashion. The system was tested using MEDLINE abstract for which the protein-protein interactions that they contain are listed in the database of interacting proteins and protein-protein interactions (DIPPPI). The system reports an F-Measure of 0.55 on test MEDLINE abstracts.